2006
DOI: 10.1017/s0022112006000929
|View full text |Cite
|
Sign up to set email alerts
|

Wave turbulence in rapidly rotating flows

Abstract: International audienceAn asymptotic quasi-normal Markovian (AQNM) model is developed in the limit of small Rossby number Ro and high Reynolds number, i.e. for rapidly rotating turbulent flow. Based on the 'slow' amplitudes of inertial waves, the kinetic equations are close to those that would be derived from Eulerian wave-turbulence theory. However, for their derivation we start from an EDQNM statistical closure model in which the velocity field is expanded in terms of the eigenmodes of the linear wave regime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
148
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 40 publications
18
148
3
Order By: Relevance
“…Indeed, each inertial wave excited by elliptical instability of the base flow can be itself unstable to a triadic resonance with another pair of inertial waves [22]: these secondary instabilities have been observed both numerically [17,23] and experimentally [24]. Whether these multiple resonances asymptotically lead to a wave turbulence regime [25,26], similar to the recently observed regimes with flexural waves in plates [27], gravity-capillary waves [28], and internal waves [29], remains to be seen. Barker and Lithwick [19], in their local model of the elliptical instability, nonetheless showed that strong geostrophic flows emerge during the saturation and disrupt the inertial wave resonances, leading instead to growth and decay cycles.…”
mentioning
confidence: 75%
“…Indeed, each inertial wave excited by elliptical instability of the base flow can be itself unstable to a triadic resonance with another pair of inertial waves [22]: these secondary instabilities have been observed both numerically [17,23] and experimentally [24]. Whether these multiple resonances asymptotically lead to a wave turbulence regime [25,26], similar to the recently observed regimes with flexural waves in plates [27], gravity-capillary waves [28], and internal waves [29], remains to be seen. Barker and Lithwick [19], in their local model of the elliptical instability, nonetheless showed that strong geostrophic flows emerge during the saturation and disrupt the inertial wave resonances, leading instead to growth and decay cycles.…”
mentioning
confidence: 75%
“…This underlying anisotropic aspect is often ignored. It is worth mentioning here some attempts at filling the gap between pure isotropic 3D and pure 2D in rotating turbulence: an asymptotic wave-turbulence approach by Bellet et al (2006) and the DNS by Liechtenstein et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Taylor-Proudman theorem has succeeded in explaining the cylindrical flow in laboratory experiments and field observations in terms of the Taylor column. However, the theorem cannot describe transitions between the Q2D and 3D flows, because energy is exchanged between the Q2D mode and the 3D mode by nonlinear mechanisms [1]. The energy transfers to the Q2D modes were demonstrated by an instability analysis [2] and weak-turbulence theory in the large-rotation limit [3].…”
mentioning
confidence: 99%